Learning the Examples Non-Examples Model with the Help of PowerPoint to Improve Learning Outcomes in IPA - Komariah, Komariah (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The objective of the research is to increase the result of learning Science through learning model of ‘examples non examples’ with power point. learning model of ‘examples non examples’ is a learning model which uses pictures related to basic competence. The result of the research obtains the increase  score and the percentage of learning exhaustiveness. On the third cycle,   the student learning exhaustiveness  obtains  80,4 %. It refers to the success indicator established. The conclusion is that through learning model of ‘examples non examples’ can increase the result of Science learning.